2016
DOI: 10.1021/acsinfecdis.6b00144
|View full text |Cite
|
Sign up to set email alerts
|

A Triazolopyrimidine-Based Dihydroorotate Dehydrogenase Inhibitor with Improved Drug-like Properties for Treatment and Prevention of Malaria

Abstract: The emergence of drug resistant malaria parasites continues to hamper efforts to control this lethal disease. Dihydroorotate dehydrogenase has recently been validated as a new target for the treatment of malaria and a selective inhibitor (DSM265) of the Plasmodium enzyme is currently in clinical development. With the goal of identifying a backup compound to DSM265, we explored replacement of the SF5-aniline moiety of DSM265 with a series of CF3-pyridinyls, while maintaining the core triazolopyrimidine scaffold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 43 publications
2
75
0
Order By: Relevance
“…Another example is reducing the molecular weight of the DSM265 to DSM421 by replacing the SF 5 ‐aniline moiety with a series of CF 3 ‐pyridinyls. DSM421 now is a new antimalarial compound with better solubility and absorption properties than DSM265 …”
Section: Effect Of Chemical Structure On Physicochemical Properties Amentioning
confidence: 99%
See 1 more Smart Citation
“…Another example is reducing the molecular weight of the DSM265 to DSM421 by replacing the SF 5 ‐aniline moiety with a series of CF 3 ‐pyridinyls. DSM421 now is a new antimalarial compound with better solubility and absorption properties than DSM265 …”
Section: Effect Of Chemical Structure On Physicochemical Properties Amentioning
confidence: 99%
“…Drug latentiation and pro‐drug formation is a classical approach to circumvent structure‐related problems via esterification, amidation, benzylation of carboxylic acid or hydroxy/amino functional groups as well as salt formation . Other chemical modification strategies include chemical substitutions to reduce molecular weight and conjugation to carrier molecule…”
Section: Chemical and Pharmaceutical Solutionsmentioning
confidence: 99%
“…The inhibition of pf DHODH has arisen as a therapeutic strategy to impede a broad range of invasive diseases, including malaria where the triazolopyrimidine‐based inhibitor, DSM265, has proceeded to clinical development . Recent studies have identified a potent derivative of DSM421, by substituting the SF 5 ‐aniline group of DSM265 with a series of CF 3 ‐pyridinyls, while retaining the main triazolopyrimidine scaffold towards inhibiting Plasmodium falciparum DHODH ( pf DHODH) . Experimental studies performed on the derivative compound DSM421 revealed improved solubility, a decrease in intrinsic clearance and a surge in plasma levels after oral dosing in comparison with DSM265.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies performed on the derivative compound DSM421 revealed improved solubility, a decrease in intrinsic clearance and a surge in plasma levels after oral dosing in comparison with DSM265. DSM421 was also shown to maintain a long‐predicted half‐life in humans . The superiority of the substituted CF 3 ‐pyridinyl to the core triazolopyrimidine scaffold resulted in the improved physical and chemical properties of DSM421 while concurrently aiding in a more simplified synthetic route as opposed to DSM265 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation